Elevation of serum lactate dehydrogenase in AL amyloidosis reflects tissue damage and is an adverse prognostic marker in patients not eligible for stem cell transplantation. (12th July 2017) - Muchtar, Eli; Dispenzieri, Angela; Lacy, Martha Q.; Buadi, Francis K.; Kapoor, Prashant; Hayman, Suzanne R.; Gonsalves, Wilson; Warsame, Rahma; Kourelis, Taxiarchis V.; Chakraborty, Rajshekhar; Russell, Stephen; Lust, John A.; et al.
Summary: The significance of serum lactate dehydrogenase (LDH) in light chain (AL) amyloidosis has not been previously explored. We studied 1019 newly diagnosed patients and correlated the elevation of LDH above the upper limit of normal (ULN) with disease characteristics and outcome. Four hundred and nine patients had an LDH above ULN, representing 40% of the study population. Patients with an elevated LDH were older, were less likely to be male and had more extensive organ involvement compared to patients with a normal LDH. Patients with high LDH had greater cardiac and renal dysfunction. Elevated LDH was an independent prognostic marker for overall survival and for death within 6 months of diagnosis, but this was restricted to patients not eligible for stem cell transplant. Serum LDH may act as a marker for organ damage and should be explored as a potential marker for tissue healing and organ recovery.